Textile wastewater treatment using Moringa oleifera seeds: optimization via polyacrylamide combination - Rendana, Muhammad; Renaldi, Fadhlurrahman; Akbar, M. Naufal; Susanti, Susi; Hardestyariki, Dwi (Program Pascasarjana Universitas Sriwijaya, 2025)
Moringa oleifera (MO) seeds have a protein with positive charges which act as cationic polyelectrolyte and active substances; rhamnosyloxy benzyl isothiocyanate. These substances are useful to reduce and adsorb pollutants and dyes in textile wastewaters. However, the use of MO seeds as a coagulant is inadequate to improve the wastewater quality. Therefore, in this study, the coagulation performance was improved by the addition of anionic polyarcylamide (PAM). Results revealed that the combination of MO+PAM showed a better performance than MO only. The removal efficiency of wastewater parameters enhanced to 88.83%, 80.58%, 19.90%, and 5.86% for dye, TSS, BOD, and COD, respectively. The addition of PAM in MO coagulant also assisted in reducing the settling time significantly (30 min). Furthermore, SEM images proved that dye solid and MO seeds combine to create clumps or flocs. Then, dye substances were drawn or trapped by the porous nature of the charge-containing MO seeds. As a whole, the use of MO+PAM give a new notion in treating textile wastewater quality.